Steady Shear Rheology of Suspensions of Mixtures of Starch Nanoparticles and Cellulose Nanocrystals - Hanie Alizadeh; Rajinder Pal (Nanomaterials)
The steady shear rheology of suspensions of mixtures of rod-shaped cellulose nanocrystals (NCC) and spherical starch nanoparticles (SNPs) was investigated experimentally over a broad range of NCC and SNP concentrations. The NCC concentration varied from about 1 to 6.7 wt% and the SNP concentration varied from 5 to 30 wt%. The suspensions of mixtures of NCC and SNPs were pseudoplastic (shear-thinning) in nature. The viscous behavior of suspensions of mixtures of NCC and SNPs could be described adequately using the power-law model. The power-law parameters, that is, consistency index and flow behavior index, were dependent on the concentrations of both NCC and SNPs. The consistency index increased substantially with increases in NCC and SNP concentrations. The flow behavior index generally decreased with an increase in NCC and SNP concentrations; that is, the suspension mixtures became more shear-thinning with increases in NCC and SNP concentrations. However, the dependence of the consistency index and flow behavior index on NCC concentration was much stronger as compared with the SNP concentration.